STUDI KRITIK PRINSIP KEHATI-HATIAN DALAM PERSPEKTIF PENCEGAHAN PEMBIAYAAN BERMASALAH PADA BANK SYARIAH - Upia Rosmalinda (Akuisisi: Jurnal Akuntansi, 2015)
Prudent banking principles representing important factor in the effort realizing healty banking system, strength and sturdy. But that way, equipment of law and regulations, especially concerning prudent banking principles in the reality not yet enough guaranted national banking quit of all its problems especially non performing loans. That is main factors the rarefaction national banking system, beside other factor like weakening of controlling of Central Bank (Bank Indonesia). There are a lot of arrangements concerning prudent banking principles in banking regulations in Indonesia, including in shariah banking system which its arrangements relate to Islamic Law.  Keyword : Prudent banking, shariah banking, non performing loans.